2021
DOI: 10.26594/register.v7i1.2042
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of e-learning readiness level of public and private universities in Central Java, Indonesia

Abstract: The development of information technology has reached into various fields, such as education. The emergence of e-learning is one manifestation of information and communication technology (ICT) in education. Until recently, only a few universities (6%) have implemented e-learning in Indonesia. Those that have implemented e-learning are still not optimally utilized. Some experts have also warned all organizations that will adopt e-learning to be concerned with thorough preparation to avoid overruns in costs. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Different models are comprised of various constructs. Some of them only used 2 constructs (e.g., Saintika et al, 2021;Mercado, 2008). However, each of the constructs has sub-factors, for instance, the administrative construct of Mercado (2008) includes commitment, policies, and instructional.…”
Section: Saintika Et Al (mentioning
confidence: 99%
“…Different models are comprised of various constructs. Some of them only used 2 constructs (e.g., Saintika et al, 2021;Mercado, 2008). However, each of the constructs has sub-factors, for instance, the administrative construct of Mercado (2008) includes commitment, policies, and instructional.…”
Section: Saintika Et Al (mentioning
confidence: 99%
“…Research conducted by Widodo et al [27] showed that students' learning readiness at the University of Mataram was still lacking due to technical constraints, such as lack of mastery of online media, lack of training, limited costs, and difficulties in accessing the internet. Meanwhile, Saintika et al [56] showed that students in the Central Java region found it difficult to learn independently. Furthermore, students' interest in learning online is still minimal.…”
Section: Student Preparednessmentioning
confidence: 99%
“…Productivity is production that is produced in a certain amount by considering the improvement in the quality of the product (Kurnia, Jaqin, et al, 2022). Technological developments in the industrial world occur very quickly, increasing the amount of production and the accuracy of delivery requires structured planning and control (Saintika et al, 2021). So the company must make significant improvements to be ready to compete in the future (Jaqin et al, 2023;Sjarifudin et al, 2022).…”
Section: Introductionmentioning
confidence: 99%